Sero-prevalence of Newcastle disease and associated risk factors in chickens at backyard chicken production Kindo Koisha, Wolaita zone, Southern Ethiopia - Wodajo, Wondimu; Mohammed, Nejib; Tora, Ephrem; Seyoum, Wasihun (Frontiers in Veterinary Science, 2023)
Newcastle disease (ND) is a serious infectious disease of poultry caused by virulent strains of Avian Paramyxovirus-1 and has a substantial impact on villages where people’s livelihood depends upon poultry farming in several developing countries including Ethiopia. In the district of the study area, no previous studies have been conducted. Thus, the aim of present study was to estimate individual and household flock level seroprevalence and risk factors for ND in unvaccinated backyard chickens in Kindo Koisha district, Wolaita zone, Ethiopia. A cross-sectional study design was conducted. For the study, household flocks were sampled as a cluster, and backyard chickens within the cluster with an age of more than 3 months were sampled. A total of 598 blood samples were collected from 86 household flocks during the study period. Serum samples were tested for ND antibodies using an Indirect-Enzyme Linked Immuno Sorbent Assay. The overall seroprevalence of ND virus at individual and flock level was 17.06% (95% CI: 14.25 – 20.29%) and 73.26% (95% CI: 62.79 - 81.64%), respectively. The ND seropositivity and associated risk factors were assessed at the individual bird and flock level by using ordinary and mixed effect logistic regression, respectively. Ordinary logistic regression revealed that crossbreed chickens had higher odds of ND seropositivity than local breeds, with an odds ratio of 2.15 (95% CI: 1.54-3.00; p<0.001). The odds of ND seropositivity was significantly higher in backyard chickens which belongs flock size greater than nine in comparison to less than nine with an odds ratio of 3.7 (95% CI: 1.12 - 12.30; p < 0.031). The potential flock risk factors related to ND seropositivity in this study were flock size, chicken house cleaning frequency, water source for chickens, dead chicken disposal practice, and distance to the next neighbor household, mixing with wild birds and owning pets. In conclusion, the current study generates significant information on the seroprevalence and the potential risk factors associated with ND at individual and flock level in Kindo Koisha district, Wolaita zone. Consequently, ND vaccination campaigns should be launched, and effective extension programs should also be provided to raise awareness about the disease.